2004
DOI: 10.1080/09603120400012868
|View full text |Cite
|
Sign up to set email alerts
|

Climatological variables and the incidence of Dengue fever in Barbados

Abstract: A retrospective study to determine relationships between the incidence of dengue cases and climatological variables and to obtain a predictive equation was carried out for the relatively small Caribbean island of Barbados which is divided into 11 parishes. The study used the weekly dengue cases and precipitation data for the years (1995 - 2000) that occurred in the small area of a single parish. Other climatological data were obtained from the local meteorological offices. The study used primarily cross correl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
92
0
12

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(120 citation statements)
references
References 0 publications
12
92
0
12
Order By: Relevance
“…Other studies in Mexico have reported similar results (Peterson et al, 2005). In Barbados, Puerto Rico and Dominica, climate variability has been linked to dengue incidence (Depradine and Lovell, 2004;Schreiber, 2001;RodriguezMorales, 2005).…”
Section: Evidences Regarding Climate Change and Its Potential Effect supporting
confidence: 69%
“…Other studies in Mexico have reported similar results (Peterson et al, 2005). In Barbados, Puerto Rico and Dominica, climate variability has been linked to dengue incidence (Depradine and Lovell, 2004;Schreiber, 2001;RodriguezMorales, 2005).…”
Section: Evidences Regarding Climate Change and Its Potential Effect supporting
confidence: 69%
“…Typically, the most significant time lags between temperature/precipitation and dengue are found to be around 1-2 months (Arcari et al, 2007;Cheong et al, 2013;Descloux et al, 2012;García et al, 2011;Gharbi et al, 2011;Gomes et al, 2012;Jeefoo et al, 2010;Lowe et al, 2011;Wu et al, 2007) , although some studies report lags of around 3-4 months (Bi et al, 2001;Chen et al, 2012;Depradine and Lovell, 2004;Yu et al, 2011) .…”
Section: Introductionmentioning
confidence: 99%
“…12 Segundo divulgado, as condições climáticas influenciam na incidência de casos de dengue, em decorrência do aumento da temperatura, da pluviosidade e da umidade do ar, por favorecer o aumento do número de criadouros disponíveis e também o desenvolvimento do mosquito. 20 Esta patologia tem acometido indivíduos de ambos os sexos, porém há registro de maior incidência em mulheres do que em homens, assim como há um maior número de casos em pessoas com faixas etárias mais elevadas. 21 Inúmeros são os fatores condicionantes para a reprodução e disseminação do Aedes aegypti.…”
Section: Resultsunclassified